2017
DOI: 10.14735/amko2017405
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related Bloodstream Infections: Do We Know All of It?

Abstract: 2 LF SZU v Bratislave, Slovenská republika 3 Oddelenie anestéziológie a intenzívnej medicíny, Národný onkologický ústav, Bratislava, Slovenská republika SouhrnVýchodiska: Infekcie krvného prúdu súvisiace s centrálnym venóznym katétrom (catheter-related bloodstream infections -CRBSI) patria k život ohrozujúcim komplikáciám. Sú spojené so zvýšenou morbiditou, mortalitou pa cientov, ako aj zvýšenými nákladmi na zdravotnú starostlivosť. Onkologickí pa cienti predstavujú obzvlášť rizikovú skupinu, a to najmä pre im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Studies have shown that the mortality rate of ICU patients with CRBSI is generally higher than those without CRBSI. 26 The mortality rate of patients with CRBSI was 46.34% in this study, with no difference in different intubation sites (P=0.24).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Studies have shown that the mortality rate of ICU patients with CRBSI is generally higher than those without CRBSI. 26 The mortality rate of patients with CRBSI was 46.34% in this study, with no difference in different intubation sites (P=0.24).…”
Section: Discussionmentioning
confidence: 49%
“…Multiple studies have demonstrated that the extension of hospital stay is one of the important factors affecting the increased nosocomial infection. 26,32 In this study, patients with CRBSI extended the LOS by a median of 20 days compared with patients without CRBSI. Therefore, the LOS of patients is positively correlated with the occurrence of nosocomial infection, and these two may be mutually causal.…”
mentioning
confidence: 68%
“…Although the incidence of CR-BSIs has decreased in the past decade, the mortality rate remains high at 12 to 25% (Antoňáková Němčíková and Bednárovská, 2017). Therefore, CR-BSIs are recognised as a healthcare priority and should not be underestimated.…”
Section: Device Complicationsmentioning
confidence: 99%
“…2 These devices are associated with around 65% of cases of deep venous thrombosis of the upper limbs, 3 and the incidence of infection is around 1.1-7.5 per 1,000 catheters inserted in cancer patients. 4 The role of vascular ultrasonography in prevention, diagnosis, and ongoing management of these types of situations is illustrated in the cases reported below.…”
Section: Introductionmentioning
confidence: 99%